Linking antibiotic resistance genes in the vaginal microbiota to health-related behaviors and antibiotic awareness in reproductive-age women: a cross-sectional study - Castellano, Paola; Ceccarani, Camilla; Djusse, Marielle Ezekielle; Mazzetti, Michela; Morselli, Sara; Camboni, Tania; Conti, Silvia; Prinelli, Federica; Severgnini, Marco; Foschi, Claudio; Dall’Asta, Margherita; Consolandi, Clarissa; et al. (Frontiers in cellular and infection microbiology, 2025)
The vaginal microbiota (VMB), predominantly shaped by species, plays a crucial role in maintaining vaginal health and preventing infections. However, its delicate balance is increasingly challenged by the widespread use of antibiotics and the consequent rise in antibiotic resistance genes (ARGs). While the VMB has been recognized as a potential reservoir for ARGs, limited research has explored how microbial composition, antibiotic exposure, and individual behavioral factors converge to shape the vaginal resistome. In this cross-sectional study, vaginal swabs were collected from 105 reproductive-age Caucasian women. The VMB composition was characterized and classified into Community State Types (CSTs), by sequencing the hypervariable V3-V4 regions of the bacterial 16S rRNA gene. In order to highlight common patterns of abundance among taxa, a co-abundance groups (CAGs) analysis was performed. We assessed the distribution of 14 ARGs conferring resistance to macrolides, tetracyclines, beta-lactams, and quinolones along with two associated transposons by means of PCR. An overall composite ARGs score was also calculated. Participants completed detailed questionnaires assessing demographics and behavioral factors, with a particular focus on both health- and antibiotic-related behaviors. Statistical analyses examined associations between ARG prevalence, vaginal microbiome composition and relevant exposures. CSTs I and III were the most prevalent, with the most frequently detected ARGs being , , , ), and , each present in over 65% of participants. ARG presence was positively correlated with a higher vaginal microbiome alpha-diversity. Moreover, BV-associated bacterial taxa showed strong associations with ARGs, while species generally exhibited negative correlations. Smoking, a higher body mass index (BMI), presence of spp. and a history of antibiotic use were significantly associated with increased ARG prevalence, whereas oral contraceptive use and higher diet quality scores were negatively associated. Correlating together the relative abundances of the microbial CAGs and the presence/absence of specific ARGs, we found a positive association between several genes related to macrolide and tetracycline resistance and the - CAG. Additionally, the - , and the CAGs were positively correlated to the total ARG score, whereas the CAG was negatively correlated. These findings underscore the role of the VMB as a dynamic reservoir of ARGs and highlight the influence of individual lifestyle and antibiotic-related behaviors on ARG dissemination in the vaginal niche. This supports the need for integrated public health strategies that combine antibiotic stewardship with targeted lifestyle and behavioral interventions, as well as the development of individualized therapeutic approaches.